2022
DOI: 10.1590/fst.08221
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Rhus Coriaria L. and Salvia Urmiensis bunge against some food-borne pathogens and identification of active components using molecular networking and docking analyses

Abstract: This research aimed to evaluate the in vitro antibacterial activity of methanol extracts of Rhus coriaria L. (sumac) and Salvia urmiensis Bunge against some food-borne pathogens, survey the phytochemical constituents of the extracts, and their activity against some drug targets in pathogens. The antibacterial activity of the extracts was evaluated against six pathogens using agar well diffusion and broth microdilution methods. Both extracts exhibited antibacterial activity and the highest activity was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Here, we found SRB strains in 60% of the samples. The significant elevation of the SRB strains had been reported to be associated with periodontal diseases (Gopalakrishnan et al, 2019). Still, different species were found in both studies that could be attributed to the study population.…”
Section: Multiplex Pcr and Sequencingmentioning
confidence: 73%
See 1 more Smart Citation
“…Here, we found SRB strains in 60% of the samples. The significant elevation of the SRB strains had been reported to be associated with periodontal diseases (Gopalakrishnan et al, 2019). Still, different species were found in both studies that could be attributed to the study population.…”
Section: Multiplex Pcr and Sequencingmentioning
confidence: 73%
“…Bacterial resistance to antimicrobials in the biofilm phase is a major global issue today. In addition, studies have shown that biofilm formation on fixed orthodontic appliances, which happens due to etching, priming, and applying brackets to the tooth surface, can cause enamel demineralization and gingival tissue inflammation (Ghane et al, 2022;Jeon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…strong antibacterial and antifungal effect [8]. This plant is traditionally used in the treatment of diabetes mellitus [9], stroke and cancer [10,11], diseases of the gastrointestinal tract [12], arterial hypertension [13].…”
Section: Ofmentioning
confidence: 99%
“…One of the botanical specimens that has attracted signi cant attention in the realm of antimicrobial research is the sumac plant, scienti cally denoted as Rhus coriaria. Numerous studies have substantiated its antimicrobial attributes (Ghane et al 2022). Nevertheless, an area that has not been extensively scrutinized pertains to the impact of sumac aqueous extract on antibiotic-resistant bacterial strains.…”
Section: Introductionmentioning
confidence: 99%